Soft tissue filler augmentation of the orbicularis retaining ligament to improve the lid‐cheek junction. (22nd October 2021) - Bernardini, Francesco P.; Casabona, Gabriela; Alfertshofer, Michael G.; Frank, Konstantin; Moellhoff, Nicholas; Gotkin, Robert H.; Davidovic, Kristina; Voropai, Daria; Valli, Andrea; Cotofana, Sebastian
Abstract: Background: The orientation of facial ligaments changes with increasing age due to the loss of bony support. Soft tissue filler injections placed in close proximity to facial ligaments can alter their orientation to help achieve an improved and younger aesthetic appearance. Objective: To assess the anatomic and aesthetic effects of a standardized injection with soft tissue filler placed directly inferior to the orbicularis retaining ligament in the infraorbital region. Methods: A total of 163 patients with signs of infraorbital aging were treated with a standardized soft tissue filler injection into and in close proximity to the orbicularis retaining ligament (ORL). 2D frontal images of the infraorbital region were rated by eleven blinded and independent raters with regards to the aesthetic appearance of the infraorbital region before and after the standardized injection treatment. Results: The aesthetic appearance of the entire infraorbital region (lid‐cheek junction) was rated before and after the treatment. The severity of the tear trough (medial aspect of the infraorbital region) as well as the hollowing of the lateral aspect of the infraorbital region also was rated before and after the treatment. Aesthetic improvement was statistically significant when evaluated by the blinded raters, the treating physician, and the patients. All the results were "very much improved" compared to baseline. Conclusion: The effectiveness of this injection technique is thought to be due to the strategic placement of soft tissue filler that helps to reposition facial ligaments that have changed their orientation during the aging process.